2011
DOI: 10.1002/pca.1316
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Antioxidants from Spruce (Picea abies) Bark using Eco‐friendly Solvents

Abstract: The study has shown that PFE is a fast and environmentally sustainable technique, using water and ethanol as solvent for the extraction of antioxidants from spruce bark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…E-Astringin and E-isorhapontin are usually the major compounds of these extracts, while E-piceid, stilbene aglycones and several dimers of stilbene glucosides have also been identified [8]. Several works have demonstrated the influence of the tree age, extraction method and distribution of chemicals within bark on the yield and activity of extracts as well as on the amount of produced stilbene glucosides and phenolic compounds [9][10][11]. Despite the high number of references regarding spruce bark bioactive compounds, there is a lack of information concerning the effective recovery and purification of these high-value compounds in sufficient amount for a potential industrial exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…E-Astringin and E-isorhapontin are usually the major compounds of these extracts, while E-piceid, stilbene aglycones and several dimers of stilbene glucosides have also been identified [8]. Several works have demonstrated the influence of the tree age, extraction method and distribution of chemicals within bark on the yield and activity of extracts as well as on the amount of produced stilbene glucosides and phenolic compounds [9][10][11]. Despite the high number of references regarding spruce bark bioactive compounds, there is a lack of information concerning the effective recovery and purification of these high-value compounds in sufficient amount for a potential industrial exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Ajuong and Berkinshaw (2004) confirmed that the ethanol extract from spruce chips contains condensed tannins, flavonoids, and phenolic compounds. Composition of extracts was confirmed in other experiments by using different types of extraction (Co et al 2011, Feng et al 2013, Krogell et al 2012. Conventional separation techniques such as solvent extraction and distillation have the drawback of leaving trace amounts of solvents or to cause thermal degradation (Ahluwalia et al, 2013).…”
Section: Introductionmentioning
confidence: 60%
“…ASE of extractive substances may be influenced by factors such as time of extraction, moisture content, particle size, solid-liquid ratio, type and composition of solvent, temperature and number of extraction cycles. The aim of Co et al (2011) paper was to obtain antioxidants from spruce bark extracts. Several compounds such as stilbene glucosides, astringin (as stilbenoid), piceid and isorhapontin were identified.…”
Section: Introductionmentioning
confidence: 99%
“…ELSD has been used widely for the detection of natural compounds lacking a chromophore, such as lipids (e.g., triglycerides, fatty acids, steryl glucosides, etc.,) (Stolyhwo et al 1985;Marcato and Cecchin 1996;Moreau et al 2008), carbohydrates (Herbreteau et al 1992;Antonopoulos et al 2004b;Nogueira et al 2005) and amino acids (Chaimbault et al 2000;Petritis et al 1999). Nevertheless, ELSD was also used for UV-absorbing compounds, such as phenolic terpens (Bicchi et al 2000) or resveratrol-like antioxidants (e.g., astringin, piceid, and isorhapontin) (Co et al 2012). With Corona CAD, the aerosol is composed of charged micro droplets.…”
Section: (A) General Aspectsmentioning
confidence: 99%